Intracapsular Tonsillectomy Using Plasma Ablation Versus Total Tonsillectomy: A Systematic Literature Review and Meta‐Analysis. Issue 1 (17th February 2023) - Sedgwick, Matthew J.; Saunders, Christopher; Bateman, Neil
Abstract: Objective: To determine whether intracapsular tonsillectomy, using plasma ablation, results in differences in postoperative patient outcomes to total tonsillectomy. Data Sources: A systematic review of two databases (Embase and PubMed) was conducted in March 2022 to identify published English‐language randomized controlled trials and observational studies which provided a comparison between intracapsular tonsillectomy, using plasma ablation, and total tonsillectomy. Review Methods: Qualitative synthesis and meta‐analysis were used to compare outcomes between techniques. Results: Seventeen studies were identified for inclusion. Across these, 1996 and 4565 patients underwent intracapsular and total tonsillectomy, respectively. Studies included 8 randomized controlled trials, 1 prospective cohort study, and 8 retrospective cohort studies. Time to pain free, time on analgesia, time to normal diet, and time to normal activity were significantly shorter with intracapsular tonsillectomy by on average 4.2 (95% confidence interval [CI] 1.5‐5.9; p < .0001), 4.1 (95% CI 2.7‐5.4; p < .0001), 3.5 (95% CI 1.7‐5.4; p = .0002) and 2.8 (95% CI 1.6‐4; p < .0001) days, respectively. Risk of posttonsillectomy hemorrhage was significantly lower following intracapsular tonsillectomy (relative risk [RR] 0.36; 95% CI 0.16‐0.81; p = .0131); risk of posttonsillectomy hemorrhage requiring surgical management was lower but failed to reach significance (RR 0.52; 95% CI 0.19‐1.39; p = .19). Conclusion: Intracapsular tonsillectomy using plasma ablation has similar efficacy in managing indications for tonsil surgery to total tonsillectomy while significantly reducing the postoperative morbidity and likelihood of posttonsillectomy hemorrhage experienced by patients, allowing them to return to their normal life faster.